The Impact Of Social Media Marketing On Buying Behavior Of Ladies - Aziz, Khanda Gharib; Jabar, Lava; Wahbi, Darya; Luqman, Rayan (Al Huwiyah: Journal of Woman and Children Studies, 2023)
Social media has impacted society in significant ways on the fiscal, political, and societal levels over the past ten years. Traditional media's impact is waning, but social media platforms are being adopted globally at an unprecedented rate, highlighting the extraordinary nature of the social media phenomenon. This study examines the effects of social media and influential personalities within social media on women’s buying behaviour, and the extent to which social media influences women’s buying behaviour. For this purpose, online survey forms were distributed to 226 women aged 18 to over 55 years. In addition to demographic information including age, education, income, marital status and social media types including Facebook, Instagram, Snapchat, WhatsApp, Twitter, and YouTube, we have six questions for the independent variable social media and five for the dependent variable setting female buying behaviour. Our data were analysed with the help of SPSS. The results show that part of women’s buying behaviour is determined by social media marketing. Other changes attributed to other factors that influence women’s buying behaviour.